Rapid Identification and Simultaneous Quantification of Aristolochic Acids by HPLC-DAD and Confirmations by MS in Aristolochia chilensis Using a Limited Biomass - Michael Araya; Samantha García; Marcia González-Teuber (Journal of Analytical Methods in Chemistry)
Six aristolochic acids were identified in the Chilean species Aristolochia chilensis using high-performance liquid chromatography coupled to a diode array detector (HPLC-DAD) and subsequent confirmation with mass spectrometry (MS). The fractions of each signal were collected and injected directly into an Orbitrap mass detector model Q Exactive Focus (Thermo Scientific). The acids extraction was done with 0.10–0.50 g of lyophilized and pulverized sample and concentrated in Soxhlet extraction equipment. The liquid-liquid separations and a subsequent solid phase extraction (SPE) C18 were performed using 100 µL of the extract that contains the aristolochic acids present in the Aristolochia chilensis plant. The HPLC conditions used a single mobile phase acetonitrile : water (1 : 1) acidified with 0.1% acetic acid and an isocratic elution to 1 mL·min−1. The column InertSustain C18 250 × 4.6 mm and 3 µm was used, the injection volume was 20 µL, and the time of run was reduced to 15 min. Calibration curves were constructed with r2 being 0.9997. The quantification limit for AAI was 0.138 ± 0.010 µg/mL, and for AAII, it was 0.558 ± 0.042 µg/mL.